Trends in the prevalence and burden of blindness and vision loss among adolescents aged 10–24 years in the Western Pacific Region over 30 years - Yunjiao Luo; Qingzhi Wang; Yingxue Wang; Louisa Esi Mackay; Na Yan; Yuhao Wang; Blen Dereje Shiferaw; Yihan Wang; Jingjing Wang; Jie Tang; Ya Liao; Xiaojuan Wang; et al. (BMC Public Health)
Abstract Background This study aimed to understand the vision health status of adolescents in the Western Pacific Region (WPR) using Global Burden of Disease (GBD) data from 1990 to 2019. Methods We conducted a comprehensive analysis of blindness and vision loss using GBD data from 1990 to 2019, analyzed trends in the prevalence and burden of blindness and vision loss over time using joinpoint regression, and analyzed their independent effects on blindness and vision loss in three dimensions using age-period-cohort (APC) modeling. Results The prevalence of blindness and vision loss among adolescents in the WPR showed an increasing trend between 1990 and 2019 (AAPC: 0.56%) and a slight increase in YLD (AAPC: 0.11%). The joinpoint regression showed a decreasing trend after 2017 (AAPC: -2.45%). The prevalence and burden trended downward in most Western Pacific countries, with only China rising significantly (AAPC prevalence: 0.57%). Refractive disorders had the highest prevalence among the subgroups. The risk of blindness and vision loss in adolescents reduced with age but grew later in time and at later birth. In addition, prevalence and burden were generally higher in females than males. Conclusions In the context of a declining global trend in the prevalence and burden of blindness and vision loss among adolescents, there is an increasing trend among adolescents in WPR, with the most pronounced rise in China. This finding has important implications for WPR, suggesting that more attention should be given to adolescent eye health in the region.